Know your enemy: Contradictory elements find synthesis in The Kingdom of Little Wounds - Jaeger, Cora (Kansas State University. K-State Libraries, 2014)
Susan Cokal's first novel for young adults, The Kingdom of Little Wounds, garnered reviews that discussed the roles of contradictory forces. While one review noted these contradictory forces were due to the novels use of fairy tale qualities along with the exploration of grim realities, the other noted that these aspects of create a thought provoking combination rather than a stark dichotomy. The development of an argument towards the novel's success depending upon a synthesis between the many forces that the novel expertly includes leads to an in-depth exploration of the nature of classic fairy tales, the influence of superstition, as well as the role of science and medicine in the sixteenth-century.
Citation: Jaeger, C. (2014). Know your enemy: Contradictory elements find synthesis in The Kingdom of Little Wounds. Unpublished manuscript, Kansas State University, Manhattan, KS.Kirmser Undergraduate Research Award - Individual Non-Freshman, honorable mention
Keywords: Fairy tale; ScienceReview; Opposing forces; Synthesis; Contradictory; Combination